Pengaruh Budaya Organisasi, Gaya Kepemimpinan dan Disiplin kerja Terhadap Kinerja Pegawai - Saputro, Ardiyanto Kusoma; Noch, Muhamad Yamin; Mustajab, Duta (Paradoks : Jurnal Ilmu Ekonomi, 2024)
This study examines the impact of organizational culture, leadership style, and work discipline on the performance of employees at the Secretariat of Puncak Jaya Regency in Central Papua. The study population comprises 176 employees within the Secretariat. Employing a quantitative descriptive approach, the research aims to delve into the interrelationships among Organizational Culture, Leadership Style, Work Discipline, and Employee Performance at the Secretariat of Puncak Jaya Regency. Using probability sampling, 35% of the total population was sampled, resulting in 62 respondents participating. The primary data source for this research is data obtained from distributing questionnaires to all respondents. The statistical method used to test the hypothesis is multiple linear regression analysis with the help of SPSS. The findings of the research reveal significant impacts. Organizational culture significantly influences the performance of employees at the Secretariat of Puncak Jaya Regency; likewise, leadership style and work discipline significantly affect employee performance. Moreover, when analyzed collectively, organizational culture, leadership style, and work discipline significantly influence employee performance. This study sheds light on the dynamics within the Secretariat of Puncak Jaya Regency and contributes to a nuanced understanding of the factors influencing employee performance.